The mitochondrial genome of the 'twisted-wing parasite' Mengenilla australiensis (Insecta, Strepsiptera): a comparative study - Kathirithamby Jeyaraney (BMC Genomics, 2009)
Abstract Background Strepsiptera are an unusual group of sexually dimorphic, entomophagous parasitoids whose evolutionary origins remain elusive. The lineage leading to Mengenilla australiensis (Family Mengenillidae) is the sister group to all remaining extant strepsipterans. It is unique in that members of this family have retained a less derived condition, where females are free-living from pupation onwards, and are structurally much less simplified. We sequenced almost the entire mitochondrial genome of M. australiensis as an important comparative data point to the already available genome of its distant relative Xenos vesparum (Family Xenidae). This study represents the first in-depth comparative mitochondrial genomic analysis of Strepsiptera. Results The partial genome of M. australiensis is presented as a 13421 bp fragment, across which all 13 protein-coding genes (PCGs), 2 ribosomal RNA (rRNA) genes and 18 transfer RNA (tRNA) sequences are identified. Two tRNA translocations disrupt an otherwise ancestral insect mitochondrial genome order. A+T content is measured at 84.3%, C-content is also very skewed. Compared with M. australiensis, codon bias in X. vesparum is more balanced. Interestingly, the size of the protein coding genome is truncated in both strepsipterans, especially in X. vesparum which, uniquely, has 4.3% fewer amino acids than the average holometabolan complement. A revised assessment of mitochondrial rRNA secondary structure based on comparative structural considerations is presented for M. australiensis and X. vesparum. Conclusions The mitochondrial genome of X. vesparum has undergone a series of alterations which are probably related to an extremely derived lifestyle. Although M. australiensis shares some of these attributes; it has retained greater signal from the hypothetical most recent common ancestor (MRCA) of Strepsiptera, inviting the possibility that a shift in the mitochondrial selective environment might be related to the specialization accompanying the evolution of a small, morphologically simplified completely host-dependent lifestyle. These results provide useful insights into the nature of the evolutionary transitions that accompanied the emergence of Strepsiptera, but we emphasize the need for adequate sampling across the order in future investigations concerning the extraordinary developmental and evolutionary origins of this group.